1981
DOI: 10.1002/iroh.19810660606
|View full text |Cite
|
Sign up to set email alerts
|

Overwintering of Invertebrates in a Shallow Northern Swedish Lake

Abstract: key uvrds : winter ecology, lake, Sweden, benthic invertebrates, Chironomidae Ahstmct During two winters, the benthic invertebrates in a shallow northern Swedish lake (66 ON) were studied. The lake is ice-covered for about 200 days a year. Live Lamellibranchiata, Oligochaeta. Hydracarina, Isopoda, Heteroptera, Cole optera and Diptera were found in samples of ice and of frozen lake-bottom sediments. During the winter in which the bottom froze deepest, a 70-90 I!,, decrease in numbers of live Chironomidae larv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…storai larvae were found in cocoons. Asellus aquaticus, on the other hand, seems to suffer from freezing effects because it has low spring values nearly everywhere in the regulation zone (Table lo), in agreement with other reports of its low freezing tolerance (DANELL, 1981;KOSKENNIEMI and SEVOLA, 1989). Oxygen depletion in near-bottom water during the winter draw down seems to be especially harmful to Asellus, whereas it is the most tolerant macrocrustacean species with respect to low pH, and it is found in natural lakes and reservoirs with low pH values (MOSSBERG and NYBERG, 1979;PAASIVIRTA and KOSKENNIEMI, 1980; RUP- PRECHT, 1992).…”
Section: Environmental Characteristicssupporting
confidence: 90%
See 1 more Smart Citation
“…storai larvae were found in cocoons. Asellus aquaticus, on the other hand, seems to suffer from freezing effects because it has low spring values nearly everywhere in the regulation zone (Table lo), in agreement with other reports of its low freezing tolerance (DANELL, 1981;KOSKENNIEMI and SEVOLA, 1989). Oxygen depletion in near-bottom water during the winter draw down seems to be especially harmful to Asellus, whereas it is the most tolerant macrocrustacean species with respect to low pH, and it is found in natural lakes and reservoirs with low pH values (MOSSBERG and NYBERG, 1979;PAASIVIRTA and KOSKENNIEMI, 1980; RUP- PRECHT, 1992).…”
Section: Environmental Characteristicssupporting
confidence: 90%
“…Many species of Chironomus, Endochironomus and Glyptotendipes common on organic bottoms of the regulated zone of L. Kyrkosjarvi (shoreline types B and C) are known to tolerate harsh winter conditions. Their larvae can be found in good condition in frozen habitats, and their mass emergence just after the thaw indicates a high survival rate against winter conditions (DANELL, 1981;KOSKENNIEMI and SEVOLA, 1989;PAASIVIRTA and KOSKENNIEMI, 1980;PATERSON and FERNANDO, 1969b). Cocoon formation is common among chironomid larvae as an adaptive strategy to stressful periods (for references see WIGGINS et al, 1980, p. 133).…”
Section: Environmental Characteristicsmentioning
confidence: 99%
“…Moreover, the larvae may leave them again after the coldest period of winter (compare Danks and Jones 1978, Table 2). Such cocoons were also commonly encountered in a lake by Danell (1981) and in a river by Olsson (1981Olsson ( , 1982, although Andrews and Rigler (1985) found that only one of the chironomid species overwintering in a high-Arctic lake, Chaetocladius sp., made winter cocoons. Winter cocoons are tightly applied to the bodies of the larvae, which are folded up within the cocoons in ways characteristic of each species (review by Danks 1971b;Madder et al 1977;Danks and Jones 1978).…”
Section: Surviving the Wintermentioning
confidence: 90%
“…Invertebrate larvae from boreal and subarctic regions typically show adaptations for overwintering and include migration to more suitable habitats or ability to freeze solid in the ice (Danell 1981, Danks 2007. Despite these potential adaptations, the invertebrate community in the upper littoral habitat is highly affected by the ice conditions (Koskenniemi 1994), with invertebrate abundances reduced by 90% from autumn to the following spring (Danell 1981).…”
Section: Discussionmentioning
confidence: 99%